Measuring The Impact Of The Effectiveness Of A Training Program According To The Dimensions Of Professional Motivation In Improving Job Satisfaction For Accountants - Kadhim Al-Abboodi, Mohammed; Fakhfakh, Mondher (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The research aims to measure the effectiveness of a training program according to the dimensions of professional motivation for accountants and its impact on improving job satisfaction by verifying the validity of the following null hypothesis: